Effects of Customized Progressive Addition Lenses vs. Single Vision Lenses on Myopia Progression in Children with Esophoria: A Randomized Clinical Trial - Xiaowei Zhu; Dongmei Wang; Naiyang Li; Feng Zhao (Journal of Ophthalmology)
Purpose. To evaluate the effect of customized progressive addition lenses (CPALs) versus single vision lenses (SVLs) on the progression of juvenile-onset myopia in children with near esophoria. Methods. Ninety-three Chinese children, aged 7–14 years with spherical equivalent refraction (SER) ranging from −0.50 to −4.00 D and near esophoria ≥2Δ, were randomly assigned into a CPALs (n = 46) and an SVLs group (n = 47) for a 2-year, double-masked, randomized trial. The primary outcome measure was the progression of myopia, as determined by cycloplegic autorefraction. A customized near addition, calculated by a regression equation, was prescribed to establish a fixed heterophoria status for each child, which was −3Δ exophoria. Results. Eighty-four (90.3%) of the 93 children completed the 2-year follow-up. The mean initial near addition lenses were 1.65 ± 0.07 D (mean ± SE). The adjusted 2-year myopia progression was 0.23 ± 0.08 D slower in the CPALs group than in the SVLs group (p=0.046). Post hoc analysis found significantly larger treatment effects for CPALs in children without myopic parents (0.47 ± 0.15 D; 95% CI: 0.18–0.76), with lower baseline myopia (0.33 ± 0.09 D; 95% CI: 0.14–0.52; p<0.05), with higher baseline accommodative lag (0.36 ± 0.11 D; 95% CI: 0.12–0.60; p<0.05), and with higher baseline near esophoria (0.30 ± 0.10 D; 95% CI: 0.12–0.48; p<0.05). Conclusion. CPALs exerted a significant but minimal protective effect against myopia progression in Chinese children with esophoric myopia, as compared with SVLs. Regulating near heterophoria and accommodative lag by near addition lenses may not be an appropriate way to prevent myopia progression.